2020
DOI: 10.1109/access.2020.2976686
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthetic Urban Dataset for Aerial Scene Understanding

Abstract: The geometric extraction and semantic understanding in bird's eye view plays an important role in cyber-physical-social systems (CPSS), because it can help human or intelligent agents (IAs) to perceive larger range of environment. Moreover, due to lack of comprehensive dataset from oblique perspective, fogend deep learning algorithms for this purpose is still in blank. In this paper, we propose a novel method to generate synthetic large-scale dataset for geometric and semantic urban scene understanding from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Cabezas et al introduced a multi-modal synthetic dataset for this purpose [45]. Gao et al created a large-scale synthetic urban dataset specifically for unmanned aerial vehicles research and demonstrated performance improvements in comparison with real aerial images [46]. Kiefer et al applied a large-scale, high-resolution synthetic dataset to object detection tasks for unmanned aerial vehicles [47].…”
Section: Synthetic Image Datasetsmentioning
confidence: 99%
“…Cabezas et al introduced a multi-modal synthetic dataset for this purpose [45]. Gao et al created a large-scale synthetic urban dataset specifically for unmanned aerial vehicles research and demonstrated performance improvements in comparison with real aerial images [46]. Kiefer et al applied a large-scale, high-resolution synthetic dataset to object detection tasks for unmanned aerial vehicles [47].…”
Section: Synthetic Image Datasetsmentioning
confidence: 99%
“…It can support more edge nodes, allowing for more efficient drone deployment and node accessibility [36,37]. This includes data relay, data-to-data communication, low latency, high data transmission rate, and other technical support for other devices connected to the fog node [38].…”
Section: The Current Land Surface Changes Analysis and The Role Of Fog Nodesmentioning
confidence: 99%
“…The latter, will first extract three one-dimensional signals out of the three feature maps. Then it will calculate the following nine features: (1) Number of zero-crossings in radial velocity, (2, 3) arguments of maximum and minimum radial velocity, (4, 5) maximum and minimum radial velocity, (6) difference between maximum and minimum angle in azimuth, (7) difference between maximum and minimum angle in elevation, (8) difference of angle in azimuth when radial velocity reached its maximum and minimum value, (9) difference of angle in elevation when radial velocity reached its maximum and minimum value. Finally, for classification we used a Multi-Layer Perceptron (MLP), with one hidden…”
Section: Processing Pipeline For Gesture Recognitionmentioning
confidence: 99%